(untitled) (gjstudies, 2017)
This research investigates the effectiveness of continuous auditing and monitoring systems in detecting fraudulent activities within the banking sector. Throughcomprehensive analysis of 2.8 million transactions across 45 financial institutionsfrom 2014-2016, this study develops a predictive framework for identifying irregular transactions, policy violations, and control breaches. The findings demonstratethat continuous monitoring systems detect fraudulent activities 4.3 times fasterthan traditional periodic audits, with a 72% improvement in detection accuracyfor sophisticated fraud schemes. The research introduces the Continuous FraudDetection Effectiveness Model (CFD-EM), which incorporates real-time analytics,behavioral pattern recognition, and adaptive learning algorithms. Statistical analysis reveals that institutions implementing advanced continuous monitoring experienced 58% reduction in fraud losses and 67% faster response times to emergingthreats. The study provides empirical evidence supporting the strategic implementation of continuous auditing technologies, with an average return on investmentof 5.2:1 through fraud prevention and operational efficiency gains. These findingshave significant implications for banking security, regulatory compliance, and theevolution of audit practices in increasingly digital financial environments.